O estudo de alguns aspectos da geometria fractal - Swiderski, Sandro Adir (2015)
In this paper it is made a study about some fractal geometry aspects, that is a new way of seeing and conceive the geometric knowledge. Specifically it is presented an approach on the fractals since the study of the first fractal shapes, the usage of the fractal terminology till present days, highlighting its properties, technical features and applicability. It is shown some of the more known fractals as the Cantor Set, Koch Snow Flake and the Sierpinski Triangle. Furthermore taking in account that this new geometry helps human being into comprehend the place where he lives and that the school is not isolated from that, we seek the fractal geometry application in mathematics concepts related to perimeter, area, sets, exponentiation, logarithms, sequences and arithmetic progressions. Therewith we discuss the topic not just a geometric curiosity but aiming to formulate a Medium Degree teacher’s support material. The theoretic support is based on the authors Janos (2008), Barbosa (2002), Mandelbrot (1998).